(untitled) (CIPEEX, 2024)
FREEDOM OF THE PRESS IS GUARANTEED CONSTITUTIONALLY, AS IS FREEDOM OF EXPRESSION AND THE RIGHT TO PRIVACY. BUT THEY OFTEN COLLIDE, AND AT THIS TIME A JUDICIAL INTERVENTION IS NECESSARY. AFTER THE FEDERAL CONSTITUTION OF 1988 NUMEROUS CHANGES OCCURRED, MAKING THESE PRIVILEGES FUNDAMENTAL IN CONTEMPORARY TIMES. THROUGH THE RELEVANCE OF THIS STUDY, IT IS PERCEIVED THAT THROUGH THE CONFLICT BETWEEN THE THEMES ADDRESSED IS POSSIBLE TO GUIDE THE IMPORTANCE OF EACH THEME. THE COMPLEX INTERSECTION BETWEEN FREEDOM OF THE PRESS AND EXPRESSION ON THE ONE HAND AND THE RIGHT TO INTIMACY ON THE OTHER HAS BEEN A POINT OF CONSTANT CONFLICT, DEBATE, OBSTACLES, OVERLAP AND CHALLENGES. THUS, IT AIMS TO EXPOSE DIFFERENT CONCEPTS OF THESE RIGHTS, FROM THE VIEW OF SEVERAL THINKERS. THIS NARRATIVE LITERATURE REVIEW WAS ELABORATED FROM THE ANALYSIS OF ARTICLES RELATED TO THE CONFLICT BETWEEN FREEDOM OF THE PRESS AND EXPRESSION AND THE RIGHT TO INTIMACY. THE SEARCH WAS CONDUCTED IN THE DATABASES OF GOOGLE SCHOLAR AND SCIELO, FOLLOWING INCLUSION CRITERIA THAT INVOLVED PUBLICATION IN PORTUGUESE, FREE ACCESS, FULL AVAILABILITY OF ARTICLES AND PUBLISHED BETWEEN THE YEARS 2018 TO 2023. DUPLICATE ARTICLES, ABSTRACTS, REVIEWS AND INCOMPLETE TEXTS WERE REMOVED, CULMINATING IN A FINAL ANALYSIS COMPOSED OF 11 ARTICLES IN FULL. WHEN EXAMINING THE BENEFITS OBTAINED AND THE IMPROVEMENTS STILL NEEDED, IT IS CLEAR THAT THE ABSENCE OF A CLEARLY DEFINED LIMIT IN THE GUARANTEES ESTABLISHED BY THE LEGISLATOR, AS PROVIDED FOR IN ART. 5TH OF THE MAJOR LAW, INCLUDING THE RIGHT TO INVIOLABILITY OF INTIMACY AND PRIVATE LIFE. IF THERE IS NO DEMARCATION OF THE BEGINNING AND THE END OF A RIGHT, IT WILL EVENTUALLY INTERFERE IN THE SPHERE OF ANOTHER RIGHT. IN VIEW OF THIS, IT IS ESSENTIAL TO OBTAIN KNOWLEDGE ABOUT THE GUARANTEES CONSOLIDATED BY THE MAGNA CARTA, WHERE THE EXERCISE OF DEMOCRACY IS DIRECTLY LINKED TO FREEDOM OF EXPRESSION, BECAUSE THIS POLITICAL REGIME ALLOWS THE FREE DEBATE OF IDEAS AND THE OPPORTUNITY TO HAVEVAST ACCESS TO INFORMATION AT ANY TIME, WHERE IT SERVES TO BUILD A CONSISTENT ARGUMENT.